Every Body Looking - Iloh, Candice (New York : Dutton Books, 2020)
In this novel in verse, a mixed-heritage dancer's coming of age within the African diaspora is shaped by abuse at the hands of a cousin, her mother's descent into addiction, and her father's efforts to create a Nigerian-inspired home in America.
Keywords: Dancers -- Juvenile fiction; African American women college students -- Juvenile fiction; Nigerian Americans -- Juvenile fiction; Sexual abuse -- Juvenile fiction; African American universities and colleges -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Family secrets -- Juvenile fiction; Self-realization -- Juvenile fiction; Dancers -- Fiction; African American women college students -- Fiction; Nigerian Americans -- Fiction; Sexual abuse -- Fiction; African American universities and colleges -- Fiction; Family problems -- Fiction; Secrets -- Fiction; Self-realization -- Fiction; Novels in verse